Exploring the challenges of accessing medication for patients with cystic fibrosis. Issue 3 (23rd September 2021) - Herbert, Sophie; Rowbotham, Nicola Jane; Smith, Sherie; Wilson, Patrick; Elliott, Zoe C; Leighton, Paul A; Duff, Alistair; Smyth, Alan Robert
Abstract : Reducing treatment burden in cystic fibrosis (CF) is the top research priority for patients and clinicians. Difficulty accessing medication is one aspect of treatment burden. We investigated this with an online survey available globally for patients with CF and healthcare professionals. Almost three quarters of patients with CF in our survey report difficulty getting repeat prescriptions on time, and most community pharmacists experience interrupted supplies of CF-specific medications. These barriers affect emotional and physical health of people with CF. Two-thirds of people with CF would like to get all their CF medication from one place, their CF centre.